Fabrication and characterization of hybrid thermoelectric materials based on aligned nanowires - Lee, Min-Jeong; Kim, Chae Yoon; Lim, Jae-Hong (Frontiers in Chemistry, 2024)
This study introduces the synthesis of a hybrid thermoelectric material with enhanced conductivity and a high Seebeck coefficient, leveraging the properties of Te nanowires (NWs) and the conductive polymer PEDOT:PSS. Te NWs were synthesized using the galvanic displacement reaction. To further enhance conductivity, Ag-Te NWs were synthesized under optimized conditions via the Ag topotactic reaction, achieving desired results within 7 minutes using ethylene glycol and AgNO3. This hybrid material exhibited an electrical conductivity of 463 S/cm, a Seebeck coefficient of 69.5 μV/K at 300 K, and a power factor of 260 μW/mK². These metrics surpassed those of conventional Te/PEDOT:PSS hybrids by a factor of 3.6, highlighting the superior performance of our approach. This study represents a significant advancement in thermoelectric materials, improving both conductivity and efficiency.